Reflexão colaborativa, ensino de Língua Portuguesa e acessibilidade linguística junto ao estudante surdo no ensino médio - Barroso, Adriana Fernandes (Universidade Federal de São Carlos, 2023)
The study aims to understand issues related to linguistic accessibility in the Portuguese language discipline for deaf students in Technological High School, within the context of remote teaching. The research involved reflections in partnership between the researchers and the dyad of the teacher and Educational Interpreter (EI) for the deaf student. The choice of collaborative reflective spiral arises from the fact that it provides conditions for knowledge construction to occur in pathways, with the principle of decision-making collectively, taking into account all participants in the research. The explicit understanding and joint consideration of pedagogical actions led each participant to review their practices. The methodological data collection procedures are organized into four spaces. Spaces 1 and 2 refer to general classes and individual sessions, conducted on the Microsoft Teams platform, while Spaces 3 and 4 relate to meetings on Google Meet among the researchers, the Portuguese language teacher, and the EI to discuss collaborative proposals. The study highlights that this perspective has led to improvements in the teaching and learning of the deaf student, particularly as Sign Language gains more prominence in reflections on teaching Portuguese as a second language. For these and other reasons, we conducted this investigation and advocate for its existence, not only as a process of training and personal/professional development for the participants but also as a project for the production of scientific knowledge and ongoing training for educators involved in the process of linguistic accessibility for deaf individuals in high school.
Collaborative reflection, teaching Portuguese and linguistic accessibility with deaf students in high school
Keywords: Educação Especial; Surdez; Ensino Médio; Educação Bilíngue; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade